Comparative studies of infrared laser and radio-frequency action on in vitro biotissues by the method of polarization sensitive optical coherence tomography - Golubyatnikov, G. Yu; Shakhova, M. A.; Snopova, L. B.; Terent’yeva, A. B.; Ignat’yeva, N. Yu; Kamensky, V. A. (Radiophysics and quantum electronics, 2010)
We make comparative studies of structural changes of in vitro biotissues subject to the infrared (IR) laser radiation and the radio-frequency field. Noninvasive diagnostics and monitoring of microstructural changes of biological tissues are performed using optical coherent tomography.